IMPLEMENTATION OF THE 5W2H TOOL IN THE PRODUCTION PROCESS TO OBTAIN RESULTS AND PROCESS IMPROVEMENTS - Cioffi, lucas gualande; Okada, Roberto Hirochi (Revista Interface Tecnológica, 2022)
The present work aims to understand how setup’s change in the production process’ machines of a food company specialized in nutritional supplements happens. It was proved through results that this exchange took a lot of time in the company’s process. After internal studies and research, the 5w2h tool was used to optimize this activity’s time. Through bibliographic review, production process, setup, quality control and assurance, 4.0 Industry and the 5w2h tool concepts are disseminated. In this work is also explained methodology and action plans in a real case in the company mentioned above. These actions optimized setup change times, increasing productivity.